Kidney pseudotumour diagnosed by emission computed tomography. Issue 6352 (13th November 1982) - Williams, E D; Parker, C
Abstract : Emission computed tomography is a new, useful imaging technique; when a rotating gamma camera capable of such imaging is used multiple adjacent transverse sections may be obtained simultaneously, from which coronal and sagittal sections may be computed. The technique was used in a man undergoing urological investigation in whom excretion urography indicated a space-occupying lesion in the left kidney. Ultrasonography and radionuclide imaging showed nothing abnormal, but emission computed tomography using a rotating gamma camera showed that functioning cortical tissue extended across the middle of the left kidney. Radiographs were therefore reviewed and ultrasonography repeated, and it was concluded that the abnormality was a hypertrophied column of Bertin. Emission tomographic imaging of the kidney is a useful adjunct to other non-invasive studies.